Articular Cartilage and Meniscus Risk Factors of Patient-Reported Outcomes 10 Years after ACL Reconstruction: A Multicenter Cohort Study (160). Issue 10 (31st October 2021) - Brophy, Robert; Huston, Laura; Briskin, Isaac; ,; Spindler, Kurt
Objectives: Articular cartilage and meniscal damage are commonly encountered and often treated at the time of anterior cruciate ligament reconstruction (ACLR). Our understanding of how these injuries and their treatment relate to outcomes of ACLR is still evolving. The purpose of this study was to assess whether articular cartilage and meniscal variables are predictive of 10-year outcomes after ACLR. We hypothesized that articular cartilage lesions and meniscus tears/treatment would be predictors of the IKDC, KOOS (all 5 subscales), and Marx activity level at 10-year follow-up after ACLR. Methods: Between 2002 and 2008, 3273 ACLR subjects were prospectively enrolled and followed longitudinally with the IKDC, KOOS, and Marx activity score completed at entry, 2, 6, and 10 years. A logistic regression model was built incorporating variables from patient demographics, surgical technique, articular cartilage injuries, and meniscus tears/treatment to determine the risk factors of IKDC, KOOS, and Marx at 10 years. Results: We completed a minimum follow-up on 77% (2530/3273) of our cohort at 10 years. The cohort was 56% male with a median age of 23 years at the time of enrollment. Incidence of concomitant pathology at the time of surgery consisted of the following: articular cartilage (medial femoral condyle [MFC]-22%, lateral femoral condyle [LFC]-15%, medial tibial plateau [MTP]-4%, lateral tibial plateau [LTP]-11%, patella-18%, trochlear-8%) and meniscal (medial-37%, lateral-46%). Variables that were predictive of 10-year outcomes included articular cartilage damage in the patellofemoral and medial compartments and previous medial meniscus surgery (6% of knees) (Table). Medial and lateral meniscus tears and treatment at the time of ACLR were not associated with 10-year outcomes. Other variables that significantly influenced 10-year outcomes included sex, race, BMI, type of reconstruction (primary vs. revision), baseline outcome scores, and MCL pathology (5.5% of knees). Conclusions: Articular cartilage injury in the patellofemoral and medial compartments at the time of ACLR and a history of medial meniscus surgery prior to ACLR are associated with 10-year ACLR outcomes. However, meniscal tears/treatment at the time of ACLR did not predict 10-year outcomes.